8. Neurophysiological comparison among tonic, high frequency and burst spinal cord simulation: Novel insights into spinal and brain mechanisms of action. Issue 12 (December 2017) - Bocci, T.; De Carolis, G.; Barloscio, D.; Parenti, L.; Valeriani, M.; Sartucci, F.
Abstract : Spinal cord Stimulation (SCS) is an effective option for neuropathic pain treatment. New technological developments, as high-frequency (HF) and Theta Burst Stimulation (TBS), have shown promising results, although putative mechanisms of action are still debated. Twenty-five patients with lower back pain were enrolled and underwent LF, HF and TBS. LEPs were recorded by using a Nd:YAG laser: amplitudes and latencies of the main two components (N1, N2/P2) were compared among different experimental conditions. Similarly, changes in Resting Motor Threshold (RMT), cortical Silent Period (cSP), Short Intracortical Inhibition (SICI) and Intracortical Facilitation (ICF) were evaluated. TBS dampened LEP amplitudes compared with LF (N1: p  = 0.016; N2/P2: p  = 0.02) and HF stimulation ( p  = 0.015; p  = 0.031); while RMT and SICI did not change among experimental conditions, TBS significantly prolonged cSP duration compared with baseline ( p  = 0.002), LF ( p  = 0.048) and HF-SCS ( p  = 0.016); both HF ( p  = 0.004) and TBS ( p  = 0.0039) increased ICF. TBS modulates the sensory-discriminative and the affective-emotional dimension of pain through distinct mechanisms, thus involving intracortical GABAergic and Glutamatergic networks. These results have implications for therapy and for the choice of the stimulation protocol.